SYNTHESIS OF SUCROSE LAURATE FROM SUCROSE AND METHYL LAURATE (COCONUT OIL) USING TRANSESTERIFICATION REACTION - CIPTA GUNAWAN 10511065, ARI
Sucrose laurate has become one of the most favourable surfactants in recent years, especially for its safety (not iritative to the skin) and its biodegradability. Sucrose laurate is included in carbohydrates-fatty acid-esters, or it is known as SFAE (Sucrose Fatty Acid Ester) in trade. Because SFAE can be synthesized from edible natural resources such as sugar and vegetable oil, and also because the product has been proved to be safe for human, in some countries, sucrose laurate is approved to be used as surfactant materials in food, cosmetic, and drug industries. In this research, sucrose laurate was synthesized by transesterification reaction of sucrose and methyl laurate (transesterification product of coconut oil and methanol from previous work). From reaction of 3,42 grams of sucrose and 2,14 grams of laurate, 4,85 grams (92,52% rendement) of white solid product was obtained. Before transesterification process was conducted, methyl laurate sample (fatty acid methyl ester product from previous work) was concentrated to separate long-chain fatty acid ester (C8-C16) from the shorter fatty acid esters (< C6) by urea complexation process. The transesterification reaction was conducted for 24 hours at 60 oC in catalytic system of Fe-NaOH. The product was washed by acetone and then by mixed solvents of ethanol : acetone : methanol = 6 : 3 : 1 (v/v/v) to remove the remaining reactants. Then, the product was characterized by FTIR and NMR spectroscopies. From infrared spectrum of the product, two absorption peaks were observed at wavenumber of 1058 and 1109 cm-1, which is inline with C-O (ester) bond of the product. Meanwhile the 1H NMR spectrum (500 MHz, D2O) shows two signals at chemical shift of 1,13 and 5,12 ppm, which are characteristic of sucrose laurate. Physical properties of the product as surfactant were investigated by measuring the surface tension and interface tension using du Nouy ring method, determination of ESI (Emulsion Stability Index), and determination of HLB (Hydrophile-Lipophile Balance) value. At concentration of 50 ppm, the results are: 31,12 dyne/cm of surface tension, 33,26 dyne/cm of interface tension (to o-xylene), and 55,56% of ESI. HLB value of the product was measured by titrimetry method and gave 15,70 value of HLB.